A patient with elderly‐onset atypical hydroa vacciniforme with an indolent clinical course. (22nd July 2015) - Nomura, H.; Suzuki, H.; Egami, S.; Yokoyama, T.; Sugiura, M.; Tomita, K.; Imada, M.; Taniguchi, K.; Yoshino, T.; Iwatsuki, K.
Summary Hydroa vacciniforme (HV) is a rare photodermatosis that mainly affects children and manifests as vesiculopapular eruptions in sun‐exposed areas without systemic symptoms. HV‐like lymphoma (HVLL) is one of the Epstein–Barr virus (EBV)‐associated lymphoproliferative disorders (LPD) of childhood. Its diagnosis is based on monoclonal T‐cell proliferation; however, its degree of malignancy is controversial owing to its variable prognosis. Elderly‐onset cases of these diseases are extremely rare, and the clinical features remain unknown. It has been shown that late onset is closely associated with a severe phenotype in EBV‐associated LPD including atypical HV. Here we describe a case of elderly‐onset atypical HV accompanied by T‐cell monoclonality, but with a very indolent clinical course. Our patient indicates a possible case with elderly‐onset atypical HV manifesting a favourable course, and that T‐cell monoclonality and age of onset cannot always predict the disease severity, and highlights the difficulty of prognosis prediction in elderly‐onset atypical HV.